Construction of prokaryotic expression system of ltB-ureB fusion gene and identification of the recombinant protein immunity and adjuvanticity - Yan, Jie (World J Gastroenterol, 2004)
AIM: To construct ltB-ureB fusion gene and its prokaryotic expression system and identify immunity and adjuvanticity of the expressed recombinant protein. METHODS: The ureB gene from a clinical Helicobacter pylori (H pylori) strain Y06 and the ltB gene from Escherichia coli (E. coli) strain 44851 were linked into ltB-ureB fusion gene by PCR. The fusion gene sequence was analyzed after T-A cloning. A prokaryotic recombinant expression vector pET32a inserted with ltB-ureB fusion gene (pET32a-ltB-ureB) was constructed. Expression of the recombinant LTB-UreB protein (rLTB-UreB) in E. coli BL21DE3 induced by isopropylthio-β-D-galactoside (IPTG) at different concentrations was detected by SDS-PAGE. Western blot assays were used to examine the immunoreaction of rLTB-UreB by a commercial antibody against whole cell of H pylori and a self-prepared rabbit anti-rUreB serum, respectively, and determine the antigenicity of the recombinant protein on inducing specific antibody in rabbits. GM(1)-ELISA was used to demonstrate the adjuvanticity of rLTB-UreB. Immunoreaction of rLTB-UreB to the UreB antibody positive sera from 125 gastric patients was determined by using ELISA. RESULTS: In comparison with the corresponding sequences of original genes, the nucleotide sequence homologies of the cloned ltB-ureB fusion gene were 100%. IPTG with different dosages of 0.1-1.0 mmol/L could efficiently induce pET32a-ltB-ureB-E. coli BL21DE3 to express the rLTB-UreB. The output of the target recombinant protein expressed by pET32a-ureB-E. coli BL21DE3 was approximately 35% of the total bacterial proteins. rLTB-UreB mainly presented in the form of inclusion body. Western blotting results demonstrated that rLTB-UreB could combine with the commercial antibody against whole cell of H pylori and anti-rUreB serum as well as induce rabbit to produce specific antibody. The strong ability of rLTB-UreB binding bovine GM(1) indicated the existence of adjuvanticity of the recombinant protein. All the UreB antibody positive sera from the patients (125/125) were positive for rLTB-UreB. CONCLUSION: A recombinant prokaryotic expression system with high expression efficiency of the target fusion gene ltB-ureB was successfully established. The expressed rLTB-UreB showed qualified immunogenicity, antigenicity and adjuvanticity. All the results mentioned above laid a firm foundation for further development of H pylori genetically engineered vaccine.